Analysis of the Role of the Creative Economy in Increasing the Income of Jangang Woven Craftsmen From an Islamic Economic Perspective (Study on Jangang Woven Crafts in Margasari, Candi Laras Selatan District, Tapin Regency) - Sri Rahmi Damayanti Aulia; S. Purnamasari; Kurniaty; Purnama Rozak (PT FORMOSA CENDEKIA GLOBAL, 2023)
The creative economy is a new economic concept that combines information and creativity that relies on ideas, ideas and knowledge from human resources as a factor of production. In this study the aim was to determine the role of the creative economy in increasing the income of the woven woven Jangg craftsmen in Margasari Kec. South Laras Temple, Kab. Tapin. The method used is descriptive qualitative research, namely by collecting data through observation, interviews, the internet, and questionnaires on research objects. The results of this study are that the creative economy of woven Jangang in Margasari kec. The South Laras Temple has a role in the income of the craftsmen, so that the existence of this woven woven can help the economy of the craftsmen.